(untitled) (Bangladesh Journal of Pharmacology, 2015)
The aim of the present study was to investigate the anticancer activity of Drimia nagarjunae (Liliaceae) extracts against Colo205 human colon cancer cell lines by SRB assay for the first time. The bulbs and leaves of the plant were sequentially extracted using solvents with increasing polarities (hexane> chloroform>ethyl acetate>methanol>water). Ethyl acetate and chloroform bulb extracts showed potent anticancer activity compared to standard, adriamycin. Both the extracts exhibited total growth inhibition of cell at 20.1 µg/mL and 32.1 µg/mL whereas adriamycin shown 33.1 µg/mL and 50% lethal concentration was found to be 61.5 µg/mL and >80 µg/mL respectively. The active extracts were subjected to GC-MS analysis for identification of phytocompounds and it showed seven and ten major compounds respectively. Therefore, the present study demonstrated that D. nagarjunae can be a promising candidate as an anticancer agent.